2021
DOI: 10.1186/s12875-021-01418-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of personalised professional relations across care sectors in achieving high continuity of care

Abstract: Background High continuity of care has a positive impact on health outcomes, but insight into the mechanisms underlying this impact is limited. Information continuity, on which our study focuses, is especially important when relational continuity is not given, which is often the case at hospital admission or hospital discharge. The aim of this study is to provide insight into the information flows between general practices and hospitals in Germany, and to identify factors associated with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
6
0
3
Order By: Relevance
“…Personal contact, i.e. via telephone, is not required and thus depends on individual motivation [25]. The legal regulation mentioned above aims at standardising and improving hospital discharges (Rahmenvertrag Entlassmanagement, § 39 Abs.…”
Section: Context In Which the Care Practice Was Implementedmentioning
confidence: 99%
“…Personal contact, i.e. via telephone, is not required and thus depends on individual motivation [25]. The legal regulation mentioned above aims at standardising and improving hospital discharges (Rahmenvertrag Entlassmanagement, § 39 Abs.…”
Section: Context In Which the Care Practice Was Implementedmentioning
confidence: 99%
“…In der Analyse wurden induktive und deduktive Schritte verbunden 1126 ▶ tab. 1 Übersicht Datenquellen/Material (Daten aus: [24,28] Das Aufgabenspektrum und das Ausmaß der Verantwortung für diese Tätigkeiten sind unterschiedlich. Einige VERAHs beschreiben sich als die Hauptbetreuenden im sCM und sehen sich in einer Koordinatoren-und Vermittlerfunktion zwischen Ärzt:innen und Patient:innen bzw.…”
Section: Datenanalyseunclassified
“…In der Analyse wurden induktive und deduktive Schritte verbunden ▶tab. 1 Übersicht Datenquellen/Material (Daten aus: [24,28] Originalarbeit Thieme [29]…”
Section: Datenanalyseunclassified
“…An interview study found that knowing each other and having personal relationships are important for effective information flow, communication, and collaboration between health professionals and, thus, for achieving patient CoC (informational and management CoC). 18 Possible underlying mechanisms could be that through recurrent interactions, a common understanding about information flow and coordination about patients is negotiated and care is, thus, improved. The impact of those relational attributes, which can be summarized under the term provider connectedness, can be measured and analyzed by applying social network analysis (SNA).…”
Section: Introductionmentioning
confidence: 99%